Effectiveness of fetal scalp stimulation test in assessing fetal wellbeing during labor, a retrospective cohort study - Farzaneh Shakouri; Linda Iorizzo; Hellen Mc Kinnon Edwards; Christina Anne Vinter; Karl Kristensen; Per-Erik Isberg; Nana Wiberg (BMC, 2020)
Abstract Background It is discussed whether fetal scalp stimulation (FSS) test is a reliable complimentary tool to cardiotocography (CTG) to assess fetal wellbeing during labor. The test is based on the assumption that a well-oxygenated fetus, in contrast to the depressed fetus, will respond to a certain stimulus. The aim of this study was to investigate the effectiveness of the FSS-test. Methods A retrospective observational study carried out Copenhagen University Hospital, Herlev, Denmark. Laboring women with singleton pregnancies in cephalic presentation after gestation week 33 and indication for fetal blood sampling (FBS) were eligible for inclusion. The FSS-test was classified as positive when an acceleration was absent at the time of FBS and negative when an acceleration was present. Lactate in scalp blood was measured by the point-of-care device LactatePro™ and pH in artery umbilical cord blood by the stationary blood gas analyzer ABL800. Lactate level < 4.2 mmol/L in scalp blood and arterial cord pH > 7.1 were cut-offs for normality. Results Three hundred eighty-five women were included. The cohort was divided by the FBS-to-delivery time: Group 1 (n = 128) ≤ 20 min, Group 2 (n = 117) 21-59 min and Group 3 (n = 140) ≥ 60 min. The proportion of FSS-positive tests differed significantly between the groups (p < 0.000). In Group 1 the sensitivity, specificity and likelihoods for scalp lactate ≥4.2 mmol/L were 81.5 (95% CI 67-90.1), 13.3 18.5 (95% CI 5.9-24.6), LHR+ 0.94 (95% CI 0.8-1.1) and LHR - 1.4 (95% CI 0.6-3.2) and for umbilical artery pH ≤ 7.10 the values were 82.6% (95% CI 61.2-95.1), 16% (95% CI 9.4-24.7), 1.0 (95% CI 0.8-1.2) and 1.1 (95% CI 0.4-3) respectively. Regardless of the FBS-to-delivery time the LHR+ for lactate ≥4.2 mmol/L increased to 1.38 (95% CI 1.2-1.6). Conclusion The effectiveness of scalp stimulation test was poor for both ruling in and out fetal hypoxia during labor. Absence of a provoked acceleration seems to be a normal phenomenon in the second stage of labor.